Positive electrode active material, positive electrode including the same, and lithium secondary battery

JP2025022869AActive Publication Date: 2025-02-14SAMSUNG SDI CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2024128610
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-08-03
Filing Date
2024-08-05
Publication Date
2025-02-14
Estimated Expiration
2044-08-05

AI Technical Summary

Benefits of technology

【0008】 本発明の一実施形態による正極活物質は、生産価格を最小化し、かつ、容量を極大化したもので、長寿命特性が確保され、高電圧での電解質との副反応が抑制される。前記正極活物質を適用したリチウム二次電池は、高電圧駆動条件でも高い初期充放電容量および効率を示すことができ、長寿命特性を実現することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025022869000001_ABST
    Figure 2025022869000001_ABST
Patent Text Reader

Abstract

To provide a positive electrode active material including a lithium nickel-manganese complex oxide, in which the price of a positive electrode material is reduced, the characteristics of high capacity and high energy density are secured, the side reaction with an electrolyte at high voltage is suppressed, and the high-voltage performance is improved, a positive electrode including this positive electrode active material, and a lithium secondary battery.SOLUTION: A positive electrode active material includes a first positive electrode active material containing a lithium nickel-manganese complex oxide in which the content of nickel is 60 mol% or more relative to 100 mol% of the entire metals excluding lithium and existing in a mode of a secondary particle formed by aggregation of a plurality of primary particles, and a second positive electrode active material in a monoparticulate form containing the similar complex oxide as above. The second positive electrode active material exists on a surface of a monoparticle, and includes a coating layer containing aluminum and yttrium. The content of aluminum in the coating layer is 0.1 to 2 mol% and the content of yttrium is 0.1 to 1 mol% relative to 100 mol% of the entire metals excluding lithium in the second positive electrode active material.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a positive electrode active material, a positive electrode containing the same, and a lithium secondary battery. [Background technology]

[0002] Lithium secondary batteries, which have high energy density and are easy to carry, are mainly used as the driving power source for mobile information terminals such as mobile phones, laptops, and smartphones. Recently, active research has been conducted on using high-energy-density lithium secondary batteries as driving power sources or power storage sources for hybrid and electric vehicles.

[0003] In order to realize lithium secondary batteries that meet these applications, various positive electrode active materials have been studied. Among them, lithium nickel oxide, lithium nickel manganese cobalt composite oxide, lithium nickel cobalt aluminum composite oxide, lithium cobalt oxide, etc. are mainly used as positive electrode active materials. However, in recent years, while the demand for large-sized, high-capacity, or high-energy density lithium secondary batteries has rapidly increased, the supply of positive electrode active materials containing the rare metal cobalt is expected to be extremely short. In other words, since cobalt is expensive and there are not many remaining reserves, it is necessary to develop positive electrode active materials that do not contain cobalt or have a reduced cobalt content. Summary of the Invention [Problem to be solved by the invention]

[0004] The present invention provides a positive electrode active material including a lithium nickel-manganese composite oxide, which ensures high capacity and high energy density characteristics while drastically reducing the price of the positive electrode material, and suppresses side reactions with an electrolyte at high voltage, thereby improving high voltage performance, as well as a positive electrode and a lithium secondary battery including the same. [Means for solving the problem]

[0005] In one embodiment of the present invention, there is provided a cathode active material including: a first cathode active material in the form of secondary particles formed by agglomeration of a plurality of primary particles, the first cathode active material including a lithium nickel-manganese composite oxide having a nickel content of 60 mol % or more relative to 100 mol % of all metals excluding lithium; and a second cathode active material in the form of a single particle, the second cathode active material including a coating layer located on a surface of the single particle and containing aluminum and yttrium, the aluminum content of the coating layer being 0.1 mol % to 2 mol % relative to 100 mol % of all metals excluding lithium, and the yttrium content of the coating layer being 0.1 mol % to 1 mol % relative to 100 mol % of all metals excluding lithium.

[0006] In another embodiment of the present invention, a positive electrode is provided that includes a positive electrode current collector and a positive electrode active material layer located on the positive electrode current collector, the positive electrode active material layer including the positive electrode active material described above.

[0007] In yet another embodiment of the present invention, there is provided a lithium secondary battery comprising the positive electrode, the negative electrode, and an electrolyte. Effect of the Invention

[0008] The positive electrode active material according to an embodiment of the present invention minimizes production costs and maximizes capacity, ensures long life characteristics, and suppresses side reactions with the electrolyte at high voltages. A lithium secondary battery using the positive electrode active material can exhibit high initial charge / discharge capacity and efficiency even under high voltage driving conditions, and can achieve long life characteristics. [Brief description of the drawings]

[0009] [Figure 1] 1 is a cross-sectional view illustrating a lithium secondary battery according to an embodiment. [Diagram 2] 1 is a scanning electron microscopy (SEM) image of a first positive electrode active material of Example 1. [Diagram 3] 1 is a SEM image of a second positive electrode active material of Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS The present invention is not limited to the embodiments described herein, but may be embodied in various different forms.

[0011] The terms used herein are merely used to describe exemplary embodiments and are not intended to limit the present invention. A singular expression includes a plural expression unless otherwise clearly indicated in the context.

[0012] As used herein, "combinations thereof" refers to mixtures, laminates, composites, copolymers, alloys, blends, reaction products, and the like of compositions.

[0013] It should be understood that the terms "including," "comprising," or "having" are intended to specify the presence of embodied features, numerals, steps, components, or combinations thereof, but do not preclude the presence or additional possibility of one or more other features, numerals, steps, components, or combinations thereof.

[0014] In the drawings, the thickness of the various layers and regions is exaggerated for clarity, and similar parts are designated by the same reference numerals throughout the specification. When a part such as a layer, film, region, plate, etc. is said to be "on" or "on" another part, this includes not only the case where it is "directly on" the other part, but also the case where there is another part between them. Conversely, when a part is said to be "directly on" another part, it means that there is no other part between them.

[0015] Further, the term "layer" as used herein includes not only a shape formed on the entire surface when observed in a plan view, but also a shape formed on a portion of the surface.

[0016] The average particle size can be measured by a method well known to those skilled in the art, for example, by using a particle size analyzer or by using a transmission electron microscope image or a scanning electron microscope image. Alternatively, the average particle size can be obtained by measuring using a dynamic light scattering method, counting the number of particles for each particle size range by performing data analysis, and then calculating the average particle size value. Unless otherwise defined, the average particle size means the diameter (D50) of particles whose cumulative volume is 50% by volume in the particle size distribution. In addition, unless otherwise defined, the average particle size can be obtained by measuring the size (diameter or major axis length) of 20 or more particles randomly from a scanning electron microscope image to obtain a particle size distribution, and taking the diameter (D50) of particles whose cumulative volume is 50% by volume in the particle size distribution as the average particle size.

[0017] As used herein, "or" is not to be construed in an exclusive sense, e.g., "A or B" is to be construed as including A, B, A+B, etc.

[0018] The term "metal" is interpreted as including general metals, transition metals, and metalloids (semimetals).

[0019] positive electrode active material In one embodiment of the present invention, there is provided a cathode active material including: a first cathode active material in the form of secondary particles formed by agglomeration of a plurality of primary particles, the first cathode active material including a lithium nickel-manganese composite oxide having a nickel content of 60 mol % or more relative to 100 mol % of all metals excluding lithium; and a second cathode active material in the form of a single particle, the second cathode active material including a coating layer located on a surface of the single particle and containing aluminum and yttrium, the aluminum content of the coating layer being 0.1 mol % to 2 mol % relative to 100 mol % of all metals excluding lithium, and the yttrium content of the coating layer being 0.1 mol % to 1 mol % relative to 100 mol % of all metals excluding lithium.

[0020] In recent years, the price of cobalt, a rare metal, has been soaring, and there is a demand for the development of positive electrode active materials that do not contain cobalt or that have a reduced cobalt content. Among these, positive electrode active materials with an olivine crystal structure such as lithium iron phosphate (LFP), lithium manganese phosphate (LMP), and lithium manganese iron phosphate (LMFP), or a spinel crystal structure such as lithium manganese oxide (LMO), have limitations in achieving high capacity due to the small amount of lithium that can be utilized within the structure. Layered nickel-manganese positive electrode active materials have excellent capacity and efficiency characteristics because they can increase the lithium content within the structure, making them suitable as materials for high-capacity batteries. However, the removal of cobalt, which plays a key role in the layered structure, reduces structural stability, increases resistance, and makes it difficult to ensure long life characteristics. In addition, the removal of cobalt accelerates side reactions between the positive electrode active material and the electrolyte under high voltage and high temperature conditions, increasing the amount of gas generated and reducing life characteristics.

[0021] In one embodiment, a first positive electrode active material in the form of secondary particles and a second positive electrode active material in the form of single particles are mixed together as a material containing a lithium nickel-manganese composite oxide, and a specific coating agent is applied to each of the first and second positive electrode active materials in a specific amount, thereby providing a positive electrode active material that achieves high capacity and high energy density, long life characteristics, and improved high voltage performance.

[0022] The average particle size of the secondary particles of the first positive electrode active material (D 50 ) is the average particle diameter (D 50 ) in the above-mentioned case. In this case, the first positive electrode active material can be expressed as large grains or large particles, and the second positive electrode active material can be expressed as small grains or small particles. By appropriately mixing the large particles in the form of secondary particles and the small particles in the form of single particles, the capacity and energy density of the nickel-manganese positive electrode can be maximized, and the life characteristics and durability can be improved.

[0023] Here, the average particle size is determined by measuring the size (diameter or major axis length) of more than 20 random particles in a scanning electron microscope image of the positive electrode active material to obtain a particle size distribution, and then calculating the diameter (D 50 ) may be taken as the average particle size.

[0024] The average particle size (D 50 The average particle diameter (D 50 ) may be, for example, 0.5 μm to 8 μm, 1 μm to 7 μm, 1.5 μm to 6 μm, or 2 μm to 5 μm. When the average particle size of each positive electrode active material falls within the above range, high capacity and high energy density can be achieved.

[0025] The first positive electrode active material is included in an amount of 60% by weight to 95% by weight, for example, 70% by weight to 90% by weight, based on 100% by weight of the first positive electrode active material and the second positive electrode active material combined. The second positive electrode active material is included in an amount of 5% by weight to 40% by weight, for example, 10% by weight to 30% by weight, based on 100% by weight of the first positive electrode active material and the second positive electrode active material combined. When the mixing ratio of the first positive electrode active material and the second positive electrode active material satisfies the above range, it is possible to increase the energy density while maximizing the capacity.

[0026] The lithium nickel-manganese composite oxide of the first positive electrode active material and the lithium nickel-manganese composite oxide of the second positive electrode active material may be the same or different from each other. The nickel content in each lithium nickel-manganese composite oxide is 60 mol% or more relative to 100 mol% of the total metals excluding lithium in the lithium nickel-manganese composite oxide, and may be, for example, 60 mol% to 80 mol%, 65 mol% to 80 mol%, 70 mol% to 80 mol%, 60 mol% to 79 mol%, 60 mol% to 78 mol%, or 60 mol% to 75 mol%, etc. When the nickel content satisfies the above range, a high capacity can be realized, and structural safety can be improved even if the cobalt content is reduced.

[0027] The manganese content may be, for example, 10 mol% to 40 mol% relative to 100 mol% of all metals excluding lithium in the lithium nickel-manganese composite oxide, and may be, for example, 10 mol% to 39 mol%, 10 mol% to 35 mol%, 10 mol% to 30 mol%, 10 mol% to 29 mol%, 15 mol% to 39 mol%, 20 mol% to 39 mol%, 20 mol% to 30%, etc. When the manganese content satisfies the above range, the positive electrode active material can improve structural stability while realizing a high capacity.

[0028] In each of the first positive electrode active material and the second positive electrode active material, the lithium nickel-manganese-based composite oxide may be a lithium nickel-manganese-aluminum-based composite oxide further containing aluminum in addition to nickel and manganese. When the composite oxide contains aluminum, it is advantageous to maintain a stable layered structure even if the cobalt element is excluded from the structure. The content of aluminum relative to 100 mol% of the lithium nickel-manganese-aluminum-based composite oxide may be 0.1 mol% or more, 0.5 mol% or more, or 1 mol% or more, for example, 1 mol% to 3 mol%, 1 mol% to 2.5 mol%, 1 mol% to 2 mol%, or 1 mol% to 1.9 mol%. When the aluminum content satisfies the above range, a stable layered structure can be maintained even if cobalt is excluded, and the problem of the structure collapsing due to charging and discharging can be suppressed, and the long life characteristics of the positive electrode active material can be realized.

[0029] The lithium nickel-manganese composite oxide of the first positive electrode active material and the lithium nickel-manganese composite oxide of the second positive electrode active material are each independently represented by Chemical Formula 1 below. [Chemical formula 1] Li a1 Ni x1 Mn y1 Al z1 M 1 w1 O 2-b1 X b1

[0030] In Chemical Formula 1, 0.9 ≤ a1 ≤ 1.8, 0.6 ≤ x1 ≤ 0.8, 0.1 ≤ y1 ≤ 0.4, 0 ≤ z1 ≤ 0.03, 0 ≤ w1 ≤ 0.3, 0.9 ≤ x1 + y1 + z1 + w1 ≤ 1.1, and 0 ≤ b1 ≤ 0.1, and M 1 is one or more elements selected from Al, B, Ba, Ca, Ce, Cr, Fe, Mg, Mo, Nb, Si, Sn, Sr, Ti, V, W, and Zr, and X is one or more elements selected from F, P, and S.

[0031] In Chemical Formula 1, 0.9 ≤ a1 ≤ 1.5, or 0.9 ≤ a1 ≤ 1.2 may also be satisfied. Further, Chemical Formula 1 may contain aluminum, and in this case, 0.6 ≤ x1 ≤ 0.8, 0.1 ≤ y1 ≤ 0.39, 0.01 ≤ z1 ≤ 0.03, and 0 ≤ w1 ≤ 0.29 can be satisfied. For example, 0.6 ≤ x1 ≤ 0.8, 0.1 ≤ y1 ≤ 0.39, 0.01 < z1 ≤ 0.03, and 0 ≤ w1 ≤ 0.29 can be satisfied.

[0032] In Chemical Formula 1, for example, 0.6 ≤ x1 ≤ 0.79, 0.6 ≤ x1 ≤ 0.78, 0.6 ≤ x1 ≤ 0.75, 0.65 ≤ x1 ≤ 0.8, or 0.7 ≤ x1 ≤ 0.79 may also be satisfied, 0.1 ≤ y1 ≤ 0.35, 0.1 ≤ y1 ≤ 0.30, 0.1 ≤ y1 ≤ 0.29, 0.15 ≤ y1 ≤ 0.39, or 0.2 ≤ y1 ≤ 0.3 may also be satisfied, 0.01 ≤ z1 ≤ 0.025, 0.01 < z1 ≤ 0.02, or 0.01 < z1 ≤ 0.019 may also be satisfied, and 0 ≤ w1 ≤ 0.28, 0 ≤ w1 ≤ 0.27, 0 ≤ w1 ≤ 0.26, 0 ≤ w1 ≤ 0.25, 0 ≤ w1 ≤ 0.24, 0 ≤ w1 ≤ 0.23, 0 ≤ w1 ≤ 0.22, 0 ≤ w1 ≤ 0.21, 0 ≤ w1 ≤ 0.2, 0 ≤ w1 ≤ 0.15, 0 ≤ w1 ≤ 0.1, or 0 ≤ w1 ≤ 0.09, etc. may also be satisfied.

[0033] The lithium nickel-manganese composite oxide may be a cobalt-free compound that does not contain cobalt or contains a very small amount of cobalt. That is, the lithium nickel-manganese composite oxide of the first positive electrode active material and the lithium nickel-manganese composite oxide of the second positive electrode active material may each independently have a cobalt content of 0 mol % to 0.01 mol % relative to 100 mol % of all metals excluding lithium.

[0034] First positive electrode active material According to an embodiment, the aluminum concentration may be uniform in the secondary particles of the first positive active material excluding the coating layer. That is, the aluminum concentration does not have a gradient from the center to the surface in the particle, or the aluminum concentration is not higher or lower in the outside than in the inside of the particle, and the aluminum is uniformly distributed in the particle. This structure is obtained by synthesizing a composite oxide using nickel-manganese-aluminum hydroxide as a precursor by using an aluminum raw material in the preparation of a precursor without further doping aluminum in the synthesis process of the positive active material. That is, the aluminum content in the inside of the primary particle may be the same or similar regardless of the position of the primary particle. If the primary particle is selected at an arbitrary position in the cross section of the secondary particle and the aluminum content is measured in the inside of the primary particle, not in the interface of the primary particle, it can be expressed that the aluminum content is the same / similar / uniform regardless of the position of the primary particle, that is, whether the primary particle is close to the center or surface of the secondary particle. In such a structure, even if cobalt is not present or is present in a very small amount, a stable layered structure can be maintained, and no aluminum by-products or aluminum aggregates are generated, thereby simultaneously improving the capacity, efficiency, and life characteristics of the positive electrode active material.

[0035] According to an embodiment, the first positive electrode active material may further include a coating layer containing aluminum and zirconium located on the surface of the secondary particle. By including an aluminum-zirconium-rich layer on the surface of the first positive electrode active material, a side reaction with the electrolyte at a high voltage is effectively suppressed, and the capacity and life characteristics at a high voltage are improved.

[0036] The aluminum content of the coating layer may be 0.1 mol% to 2 mol%, and the zirconium content of the coating layer may be 0.05 mol% to 1 mol%, based on 100 mol% of the total metals excluding lithium in the first positive electrode active material. The aluminum content of the coating layer in the first positive electrode active material may be, for example, 0.2 mol% to 1.9 mol%, 0.3 mol% to 1.8 mol%, 0.5 mol% to 1.5 mol%, or 0.8 mol% to 1.3 mol%. The aluminum or zirconium content in the coating layer may be measured, for example, by SEM-EDS analysis of the surface or cross section of the positive electrode active material. When the aluminum content in the coating layer satisfies the above range, it is possible to form a coating layer with a uniform and thin thickness, the resistance of the positive electrode active material does not increase, and side reactions with the electrolyte are effectively suppressed, thereby improving the life characteristics of the lithium secondary battery at high voltage.

[0037] The zirconium content of the coating layer of the first positive electrode active material may be, for example, 0.1 mol% to 1 mol%, 0.1 mol% to 0.9 mol%, 0.1 mol% to 0.8 mol%, or 0.1 mol% to 0.6 mol%. When the zirconium content satisfies the above range, the positive electrode active material forms a good coating layer without a decrease in capacity or an increase in resistance, effectively suppresses side reactions with the electrolyte, and further improves capacity characteristics and life characteristics under high voltage driving conditions.

[0038] The coating layer of the first positive electrode active material may further include yttrium in addition to aluminum and zirconium. In this case, the content of yttrium may be 0.1 mol % to 1 mol % based on 100 mol % of all metals excluding lithium of the first positive electrode active material.

[0039] The coating layer of the first positive electrode active material may be in the form of a film that continuously surrounds the surface of the secondary particle, for example, in the form of a shell that surrounds the entire surface of the secondary particle. This is distinguished from a structure in which only a part of the surface of the secondary particle is partially coated. According to one embodiment, the coating layer is formed in a form that entirely surrounds the surface of the secondary particle, and can be formed to a very thin and uniform thickness, so that the positive electrode active material has improved structural stability without increasing resistance or decreasing capacity, effectively suppresses side reactions with the electrolyte, reduces the amount of gas generation under high voltage and high temperature conditions, and achieves long life characteristics.

[0040] The thickness of the coating layer of the first positive electrode active material may be 30 nm to 500 nm, for example, 30 nm to 450 nm, 30 nm to 400 nm, 30 nm to 350 nm, 30 nm to 300 nm, 30 nm to 250 nm, 30 nm to 200 nm, 30 nm to 150 nm, 50 nm to 500 nm, 80 nm to 500 nm, or 100 nm to 500 nm. When the coating layer satisfies the above thickness range, the coating can improve the structural stability of the positive electrode active material without increasing the resistance or decreasing the capacity, and can effectively suppress side reactions with the electrolyte. The thickness of the coating layer can be measured, for example, by TOF-SIMS, XPS, or EDS analysis, and the thickness range of the coating layer can be measured by TEM-EDS line profile.

[0041] The coating layer of the first positive electrode active material is characterized by being thin and uniform in thickness, with a thickness of tens to hundreds of nanometers. For example, the deviation in thickness of the coating layer within one positive electrode active material particle may be 20% or less, 18% or less, or 15% or less. Here, the deviation in thickness of the coating layer refers to the thickness of the coating layer within one positive electrode active material particle. The deviation in thickness of the coating layer means, for example, that the thickness of 10 or more points is measured in an electron microscope image of a cross section of one positive electrode active material particle, the arithmetic average is calculated, and the absolute value of the difference between one data and the arithmetic average is divided by the arithmetic average and multiplied by 100. The deviation or standard deviation of the thickness of the coating layer satisfies the above range, which means that a coating layer of uniform thickness is successfully formed in the form of a film on the surface of the positive electrode active material particle, thereby improving the structural stability of the positive electrode active material, effectively suppressing side reactions with the electrolyte, and minimizing the increase in resistance and the decrease in capacity due to the coating.

[0042] Meanwhile, in the process of forming the coating layer, aluminum may be diffused into the secondary particles. Thus, the positive electrode active material according to an embodiment may further include a grain boundary coating portion containing aluminum located on the surface of the primary particle inside the secondary particle. The interior of the secondary particle may refer to the entire interior except for the surface of the secondary particle, or may refer to a region from the surface of the secondary particle toward the center of the secondary particle to about 60% of the length of the radius. The grain boundary coating portion is a concept distinct from the coating layer on the surface of the secondary particle, and refers to a coating portion formed on the surface of the primary particle located inside the secondary particle. The presence of the grain boundary coating portion may be confirmed by SEM-EDS analysis of the cross section of the positive electrode active material. The formation of the aluminum grain boundary coating portion further stabilizes the structure of the positive electrode active material, improving the life characteristics.

[0043] The aluminum content in the grain boundary coating portion is not particularly limited, and as an example, the aluminum content in the grain boundary coating portion may be less than the aluminum content in the coating layer.

[0044] Meanwhile, the aluminum content of the coating layer of the first positive electrode active material may be higher than the aluminum content of the coating layer of the second positive electrode active material described later. For example, the aluminum content of the coating layer of the first positive electrode active material and the aluminum content of the coating layer of the second positive electrode active material may be 5:1 to 2:1, or 4:1 to 2:1 in molar ratio. In this case, the aluminum of the coating layers of the first and second positive electrode active materials does not act as a resistor, and the capacity and life characteristics at high voltages can be maximized while improving the structural stability of each.

[0045] Second positive electrode active material The term "single particle" of the second positive electrode active material means that the particle does not have a grain boundary and exists alone, and may mean a single particle, a monolith structure, a single body structure, or a non-aggregated particle in which the particles are morphologically present in an independent phase without mutual aggregation, and may be, for example, a single crystal.

[0046] The second positive electrode active material includes a coating layer located on the surface of the single particle and containing aluminum and yttrium, the aluminum content of the coating layer being 0.1 mol% to 2 mol%, and the yttrium content of the coating layer being 0.1 mol% to 1 mol%. When both aluminum and yttrium are contained in the coating layer of the second positive electrode active material and each of them satisfies the above content range, the initial discharge capacity and life characteristics at high voltage of the positive electrode active material according to one embodiment may be maximized.

[0047] The aluminum content in the coating layer of the second positive electrode active material is 0.1 mol% to 2 mol% relative to 100 mol% of the total metals excluding lithium in the second positive electrode active material, and may be, for example, 0.2 mol% to 1.9 mol%, 0.3 mol% to 1.8 mol%, 0.5 mol% to 1.5 mol%, or 0.8 mol% to 1.3 mol%. This means only the content of aluminum contained in the coating layer separately from the aluminum contained inside the single particle. The aluminum content in the coating layer can be measured, for example, by SEM-EDS analysis of the surface or cross section of the positive electrode active material. When the aluminum content in the coating layer satisfies the above range, it is possible to form a coating layer with a uniform and thin thickness, the resistance of the positive electrode active material does not increase, side reactions with the electrolyte are effectively suppressed, and the life characteristics of the lithium secondary battery under high voltage and high temperature conditions can be improved. For example, if the aluminum content of the coating layer is too high, a uniform coating layer may not be formed or the resistance may increase, resulting in reduced charge / discharge efficiency and reduced life characteristics. Conversely, if the aluminum content of the coating layer is too low, a coating layer of appropriate thickness may not be formed, resulting in reduced effect of suppressing side reactions with the electrolyte.

[0048] The yttrium content in the coating layer of the second positive electrode active material is 0.1 mol% to 1 mol% relative to 100 mol% of the total metals excluding lithium in the second positive electrode active material, and may be, for example, 0.1 mol% to 0.9 mol%, 0.1 mol% to 0.8 mol%, 0.1 mol% to 0.6 mol%, 0.1 mol% to 0.4 mol%, or 0.1 mol% to 0.3 mol%. When the yttrium content satisfies the above range, the positive electrode active material forms a good coating layer without a decrease in capacity or an increase in resistance, and effectively suppresses side reactions with the electrolyte, and effectively reduces the amount of gas generated under high voltage or high temperature conditions.

[0049] The second positive electrode active material is characterized in that both aluminum and yttrium are contained in the coating layer, which can improve capacity characteristics and life characteristics at high voltages compared to when only one of the two is contained.

[0050] The coating layer of the second positive electrode active material may be in the form of a film that continuously surrounds the surface of the single particle, for example, in the form of a shell that surrounds the entire surface of the single particle. This is distinguished from a structure in which only a part of the surface of the particle is partially coated. According to one embodiment, the coating layer may be formed to a very thin and uniform thickness while being formed in a form that entirely surrounds the surface of the single particle, so that the positive electrode active material has improved structural stability without increasing resistance or decreasing capacity, and side reactions with the electrolyte are effectively suppressed, thereby realizing long life characteristics at high voltage.

[0051] The thickness of the coating layer of the second positive electrode active material may be 30 nm to 500 nm, for example, 30 nm to 450 nm, 30 nm to 400 nm, 30 nm to 350 nm, 30 nm to 300 nm, 30 nm to 250 nm, 30 nm to 200 nm, 30 nm to 150 nm, 50 nm to 500 nm, 80 nm to 500 nm, or 100 nm to 500 nm. When the coating layer satisfies the above thickness range, the coating can improve the structural stability of the positive electrode active material without increasing the resistance or decreasing the capacity, and can effectively suppress side reactions with the electrolyte. The thickness of the coating layer can be measured, for example, by TOF-SIMS, XPS, or EDS analysis, and the thickness range of the coating layer can be measured by TEM-EDS line profile.

[0052] The coating layer of the second positive electrode active material is characterized by being thin and uniform in thickness, with a thickness of tens to hundreds of nanometers. For example, the deviation in thickness of the coating layer within one positive electrode active material particle may be 20% or less, 18% or less, or 15% or less. Here, the deviation in thickness of the coating layer refers to the thickness of the coating layer within one positive electrode active material particle. The deviation in thickness of the coating layer may be, for example, obtained by measuring the thickness at 10 or more points in an electron microscope image of a cross section of one positive electrode active material particle, calculating the arithmetic average, dividing the absolute value of the difference between one data and the arithmetic average value by the arithmetic average value, and multiplying the result by 100. The deviation or standard deviation of the thickness of the coating layer satisfying the above range means that a coating layer of uniform thickness is successfully formed in the form of a film on the surface of the positive electrode active material particle, thereby improving the structural stability of the positive electrode active material, effectively suppressing side reactions with the electrolyte, and minimizing the increase in resistance and the decrease in capacity due to the coating.

[0053] In the coating layer of the second positive electrode active material, aluminum may exist in a continuous film form and yttrium may exist in an island form, depending on the characteristics of each element.

[0054] In one embodiment, aluminum and yttrium may be mixed in one coating layer, and in this case, aluminum may be present in the form of a continuous film and yttrium may be present in the form of islands, but the forms are not limited thereto.

[0055] In another embodiment, aluminum and yttrium may form separate layers. For example, the second positive electrode active material may include a first coating layer containing aluminum located on the surface of the single particle, and a second coating layer containing yttrium located on the first coating layer. Aluminum is first attached or absorbed on the surface of the single particle to form a thin film-type first coating layer, and yttrium is coated on the first coating layer to form a second coating layer. Of course, aluminum and yttrium may be mixed in the first coating layer and the second coating layer, but the first coating layer may be an aluminum-rich coating layer mainly composed of aluminum, and the second coating layer may be an yttrium-rich coating layer mainly composed of yttrium. In this case, yttrium may be present in the second coating layer in the form of islands, but is not particularly limited.

[0056] The thickness of the first coating layer and the second coating layer is not particularly limited, but the thickness of the first coating layer may be 10 nm to 200 nm, for example, 20 nm to 200 nm, 30 nm to 200 nm, or 30 nm to 180 nm. The thickness of the second coating layer may be 20 nm to 300 nm, for example, 20 nm to 250 nm, 20 nm to 200 nm, 30 nm to 300 nm, or 50 nm to 300 nm. When each thickness satisfies the above range, the structural stability of the positive electrode active material can be improved without increasing the resistance or decreasing the capacity due to the coating, and the side reaction with the electrolyte can be effectively suppressed to improve the life characteristics at high voltage.

[0057] In the positive electrode active material according to an embodiment, the content of cobalt may be, for example, 0.01 mol % or less, 0.005 mol % or less, 0.001 mol % or less, for example, 0 mol % to 0.01 mol %, relative to 100 mol % of all metals excluding lithium. The positive electrode active material according to an embodiment may be, for example, a cobalt-free positive electrode active material.

[0058] In one embodiment, the other positive electrode active material does not contain sodium. Although sodium ions can be used in a process for manufacturing a positive electrode active material, a manufacturing method described below can be used to form positive electrode active material particles with a stable structure and a coating layer with a uniform thickness without using sodium ions.

[0059] Method for producing positive electrode active material In one embodiment, the present invention provides a method for producing a positive electrode active material, comprising: (i) mixing a nickel-manganese composite hydroxide having a nickel content of 60 mol % or more relative to 100 mol % of the total metals and a lithium raw material, and heat-treating the mixture to prepare a first positive electrode active material in the form of secondary particles formed by aggregation of a plurality of primary particles; (ii) mixing a nickel-manganese composite hydroxide having a nickel content of 60 mol % or more relative to 100 mol % of the total metals and a lithium raw material, and heat-treating the mixture to obtain a lithium nickel-manganese composite oxide in the form of single particles, introducing the obtained lithium nickel-manganese composite oxide into a solution obtained by mixing an aluminum raw material and an yttrium raw material in an aqueous solvent, mixing the resulting lithium nickel-manganese composite oxide, drying the resulting solution, and heat-treating the mixture again to prepare a second positive electrode active material; and (iii) mixing the first positive electrode active material and the second positive electrode active material. Here, in the second positive electrode active material preparation step, the aluminum content in the aluminum raw material is 0.1 mol % to 2 mol % relative to 100 mol % of the total metals excluding lithium in the second positive electrode active material, and the yttrium content in the yttrium raw material is 0.1 mol % to 1 mol % relative to 100 mol % of the total metals excluding lithium in the second positive electrode active material. The above-mentioned positive electrode active material can be produced by the above method.

[0060] In the respective preparation steps of the first positive electrode active material and the second positive electrode active material, the nickel-manganese composite hydroxide may contain no cobalt or may contain a very small amount of cobalt, and may be, for example, a cobalt-free nickel-manganese composite hydroxide, for example, a cobalt-free nickel-manganese-aluminum composite hydroxide. The nickel-manganese composite hydroxide may be produced by a general coprecipitation method.

[0061] The nickel content in the nickel-manganese composite hydroxide is 60 mol% or more relative to 100 mol% of the total metal, and may be, for example, 60 mol% to 80 mol%, 65 mol% to 80 mol%, 70 mol% to 80 mol%, 60 mol% to 79 mol%, 60 mol% to 78 mol%, or 60 mol% to 75 mol%, etc. When the nickel content satisfies the above range, a high capacity can be achieved, and structural safety can be improved even if the cobalt content is reduced.

[0062] The manganese content in the nickel-manganese composite hydroxide may be 10 mol% to 40 mol%, 10 mol% to 39 mol%, 10 mol% to 35 mol%, 10 mol% to 30 mol%, 10 mol% to 29 mol%, 15 mol% to 39 mol%, 20 mol% to 39 mol%, 20 mol% to 30%, etc., relative to 100 mol% of the total metal.

[0063] In addition, when the nickel-manganese composite hydroxide further contains aluminum, the aluminum content may be 0.1 mol% or more, 0.5 mol% or more, or 1 mol% or more, for example, 1 mol% to 3 mol%, 1 mol% to 2.5 mol%, 1 mol% to 2 mol%, or 1 mol% to 1.9 mol%, based on 100 mol% of the total metal. When the manganese and aluminum contents in the composite hydroxide satisfy the above ranges, the structural safety of the positive electrode active material can be improved while realizing a high capacity, and the production cost can be reduced to improve the economic efficiency.

[0064] In the nickel-manganese composite hydroxide, the cobalt content may be 0.01 mol% or less, 0.005 mol% or less, or 0.001 mol% or less, based on 100 mol% of the total metals. Such a nickel-manganese composite hydroxide can avoid the increase in unit price due to cobalt, is economical, maximizes capacity, and improves structural stability.

[0065] An example of the nickel-manganese composite hydroxide is represented by the following chemical formula 2. [Chemical formula 2] Ni x2 Mny2 Al z2 M 2 w2 (OH)2

[0066] In the chemical formula 2, 0.6≦x2≦0.8, 0.1≦y2≦0.40≦z2≦0.03, 0≦w2≦0.3, and 0.9≦x2+y2+z2+w2≦1.1; M 2 is one or more elements selected from Al, B, Ba, Ca, Ce, Cr, Fe, Mg, Mo, Nb, Si, Sn, Sr, Ti, V, W, and Zr.

[0067] In the above Chemical Formula 2, for example, 6≦x2≦0.8, 0.1≦y2≦0.39, 0.01≦z2≦0.03, and 0≦w2≦0.29 may be satisfied.

[0068] The nickel-manganese composite hydroxide is in the form of particles, and the average particle size (D 50 ) may be 10 μm to 18 μm, 11 μm to 16 μm, or 12 μm to 15 μm.

[0069] In the first positive electrode active material preparation process, aluminum is not further doped, and instead, an aluminum raw material is used in the preparation of the precursor, so that a nickel-manganese-aluminum composite hydroxide in which aluminum is evenly dispersed within the structure can be used as the precursor. By using such a precursor, a positive electrode active material that does not contain cobalt and that stably maintains a layered structure even after repeated charging and discharging can be produced, and aluminum by-products and aluminum aggregates are not formed, thereby improving the capacity, efficiency, and life characteristics of the positive electrode active material.

[0070] In the preparation step of the first positive electrode active material, the nickel-manganese composite hydroxide and the lithium raw material may be mixed in a molar ratio of 1:0.9 to 1:1.8, for example, 1:0.9 to 1:1.5 or 1:0.9 to 1:1.2. The heat treatment after mixing may be performed in an oxygen atmosphere, for example, at a temperature range of 750°C to 950°C, 780°C to 900°C, or 810°C to 890°C, for 2 hours to 20 hours, or 4 hours to 12 hours. The heat treatment may produce a lithium nickel-manganese composite oxide. The obtained composite oxide may contain nickel at 60 mol% or more, for example, 60 mol% to 80 mol%, relative to 100 mol% of the total metal, and may contain no cobalt or a very small amount of 0.01 mol% or less.

[0071] According to an embodiment, the method for manufacturing a positive electrode active material may further include a step of coating after obtaining a lithium nickel-manganese composite oxide in the step of preparing a first positive electrode active material. The lithium nickel-manganese composite oxide has a significantly different content of residual lithium on the particle surface from existing nickel-based oxides of other compositions, such as lithium nickel-cobalt-manganese composite oxide and lithium nickel-cobalt-aluminum composite oxide, and has various different surface properties, so that existing coating methods cannot form a good coating layer with a uniform film shape. According to an embodiment, a method is provided for improving high voltage characteristics by forming a uniform coating layer with a very thin thickness on the surface of a lithium nickel-manganese composite oxide having an extremely small cobalt content and a nickel content of 60 mol% or more. For example, an aluminum raw material is mixed in an aqueous solvent, and then the lithium nickel-manganese composite oxide is mixed, followed by drying and reheating, to form a coating layer according to an embodiment. This may be a wet coating method.

[0072] The aqueous solvent may include distilled water, an alcohol-based solvent, or a combination thereof. The aluminum raw material may include, for example, aluminum nitrate, aluminum sulfate, aluminum carbonate, aluminum hydroxide, or a combination thereof. As an example, the aluminum raw material may include aluminum sulfate, which is advantageous in forming a coating layer having a uniform thickness on the surface of the lithium nickel-manganese composite oxide particles. The aluminum content in the aluminum raw material is 0.1 mol% to 2 mol% relative to 100 mol% of the total metals excluding lithium in the first positive electrode active material, for example, 0.2 mol% to 1.9 mol%, 0.3 mol% to 1.8 mol%, 0.5 mol% to 1.5 mol%, or 0.8 mol% to 1.3 mol%.

[0073] The solution in which the aluminum raw material is mixed with the aqueous solvent may have a pH of 1.5 to 3.5, for example, 2.0 to 3.4, 2.5 to 3.3, 2.7 to 3.3, or 2.9 to 3.2. The lithium nickel-manganese composite oxide is dropped into the aqueous solvent in which the aluminum raw material is mixed, and mixing can be performed for about 5 to 80 minutes, or 5 to 60 minutes, or 5 to 40 minutes. The pH of the mixed solution after stirring may be 4.5 to 8.5, for example, 5.0 to 8.0, 5.5 to 7.5, or 6.0 to 7.0. When such conditions are satisfied, it is advantageous to form a coating layer of uniform thickness.

[0074] The reheat treatment is a step of forming a coating layer, and can be performed, for example, in an oxygen atmosphere at a temperature range of 700° C. to 850° C., 750° C. to 840° C., or 800° C. to 830° C. for 2 to 20 hours, or 3 to 10 hours.

[0075] In addition to aluminum, a zirconium raw material can be added to the material obtained after the drying process and then reheated in order to coat it with zirconium. The zirconium raw material can be, for example, zirconium oxide, and can be added so that the zirconium content is 0.05 mol % to 1 mol % relative to 100 mol % of the metals excluding lithium in the first positive electrode active material.

[0076] In the preparation step of the second positive electrode active material, the nickel-manganese composite hydroxide and the lithium raw material may be mixed in a molar ratio of 1:0.9 to 1:1.8, for example, in a molar ratio of 1:0.9 to 1:1.5 or 1:0.9 to 1:1.2. The heat treatment after mixing these may be performed in an oxygen atmosphere, for example, in a temperature range of 750°C to 950°C, or 780°C to 900°C, or 810°C to 890°C, for 2 hours to 20 hours, or 4 hours to 12 hours. The heat treatment may produce a lithium nickel-manganese composite oxide. The obtained composite oxide may contain nickel at 60 mol% or more, for example, 60 mol% to 80 mol%, relative to 100 mol% of the total metal, and may contain no cobalt or a very small amount of 0.01 mol% or less. In order to obtain a single particle form, a process of pulverizing the lithium nickel-manganese composite oxide after production may be further included.

[0077] The second positive electrode active material in the form of a single particle cannot be coated with aluminum and yttrium by using an existing coating method, but can be coated with a good coating layer in the form of a uniform film by using a wet coating method according to an example. That is, the second positive electrode active material can be manufactured by adding and mixing the obtained lithium nickel-manganese composite oxide in the form of a single particle into a solution in which aluminum raw material and yttrium raw material are mixed in an aqueous solvent, and then drying and re-heating the mixture.

[0078] The details of the aqueous solvent and the aluminum raw material are as described above. The aluminum content in the aluminum raw material is 0.1 mol% to 2 mol% relative to 100 mol% of the total metals excluding lithium in the second positive electrode active material, for example, 0.2 mol% to 1.9 mol%, 0.3 mol% to 1.8 mol%, 0.5 mol% to 1.5 mol%, or 0.8 mol% to 1.3 mol%. The yttrium raw material may include, for example, yttrium nitrate, yttrium sulfate, yttrium carbonate, yttrium hydroxide, or a combination thereof. The yttrium content in the yttrium raw material is 0.1 mol% to 1 mol% relative to 100 mol% of the total metals excluding lithium in the second positive electrode active material, for example, 0.1 mol% to 0.9 mol%, 0.1 mol% to 0.8 mol%, 0.1 mol% to 0.6 mol%, 0.1 mol% to 0.4 mol%, or 0.1 mol% to 0.3 mol%. By containing the content of the coating raw material in the above ranges, a coating layer having a thin thickness of tens to hundreds of nanometers and a uniform thickness can be formed, and the amount of gas generation of the lithium secondary battery under high voltage driving conditions can be reduced, and high capacity and long life characteristics can be improved.

[0079] The solution in which the aluminum raw material and the yttrium raw material are mixed in an aqueous solvent may have a pH of 1.5 to 3.5, for example, 2.0 to 3.4, 2.5 to 3.3, 2.7 to 3.3, or 2.9 to 3.2. The lithium nickel-manganese composite oxide may be dropped into the aqueous solvent in which the aluminum raw material and the yttrium raw material are mixed and mixed for about 5 to 80 minutes, or 5 to 60 minutes, or 5 to 40 minutes. The pH of the mixed solution after stirring may be 4.5 to 8.5, for example, 5.0 to 8.0, 5.5 to 7.5, or 6.0 to 7.0. When such conditions are satisfied, it is advantageous to form a coating layer of uniform thickness.

[0080] Drying after the mixing step is a step of removing the solvent, and can be carried out, for example, at 40°C to 240°C, 100°C to 220°C, or 150°C to 200°C. Reheat treatment is a step of forming a coating layer, and can be carried out, for example, in an oxygen atmosphere at a temperature range of 700°C to 850°C, 750°C to 840°C, or 800°C to 830°C for 2 hours to 20 hours, or 3 hours to 10 hours. The reheat treatment temperature may be lower than the above-mentioned heat treatment temperature, and the reheat treatment time may be the same as or even shorter than the above-mentioned heat treatment time. By carrying out the reheat treatment under such conditions, a desired coating layer can be obtained. In one embodiment, the single particle type second positive electrode active material may be coated with aluminum and yttrium by a dry coating method, and the coating raw material in the dry coating method may be, for example, aluminum oxide and yttrium oxide.

[0081] The first and second positive electrode active materials may be mixed in a weight ratio of 60:40 to 95:5, for example, 70:30 to 90:10. When mixed in such a ratio, the energy density can be maximized while improving the capacity and life characteristics.

[0082] positive electrode In one embodiment, the positive electrode includes a positive electrode current collector and a positive electrode active material layer disposed on the positive electrode current collector, the positive electrode active material layer including the positive electrode active material described above. The positive electrode active material layer may further include other types of positive electrode active materials in addition to the positive electrode active materials described above. The positive electrode active material layer may also optionally include a binder, a conductive material, or a combination thereof.

[0083] According to one embodiment, the loading level of the positive electrode active material layer is 10 mg / cm 2 ~40mg / cm 2 For example, 10 mg / cm 2 ~30mg / cm 2 or 10 mg / cm 2~20mg / cm 2 In addition, the density of the positive electrode active material layer in the final rolled positive electrode may be 3.5 g / cc to 3.7 g / cc, for example, 3.5 g / cc to 3.6 g / cc or 3.5 g / cc to 3.58 g / cc. When the positive electrode active material according to an embodiment is applied, it is advantageous to realize such a loading level and positive electrode density, and a positive electrode satisfying the above-mentioned ranges of loading level and positive electrode density is suitable for realizing a lithium secondary battery with a high capacity and high energy density.

[0084] binder The binder serves to make the positive electrode active material particles adhere well to each other and to make the positive electrode active material adhere well to the current collector. Representative examples of the binder include, but are not limited to, polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, (meth)acrylated styrene-butadiene rubber, epoxy resin, (meth)acrylic resin, polyester resin, nylon, etc.

[0085] Conductive material The conductive material is used to impart electrical conductivity to the electrodes, and any material that does not cause a chemical change in the battery that is constructed and is electronically conductive can be used. Examples of the conductive material include carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, ketjen black, carbon fibers, carbon nanofibers, and carbon nanotubes; metal-based materials containing copper, nickel, aluminum, silver, and the like in the form of metal powder or metal fibers; conductive polymers such as polyphenylene derivatives; and mixtures thereof.

[0086] The content of the binder and the conductive material may be 0.5% by weight to 5% by weight, or 0.5% by weight to 3% by weight, respectively, relative to 100% by weight of the positive electrode active material layer.

[0087] The positive electrode current collector can be made of Al, but is not limited to this.

[0088] Lithium secondary battery In one embodiment, a lithium secondary battery is provided that includes the positive electrode, the negative electrode, and the electrolyte described above.

[0089] Lithium secondary batteries can be classified into cylindrical, square, pouch, coin, etc. types according to their shapes. FIG. 1 is a schematic diagram showing a lithium secondary battery according to an embodiment. Referring to FIG. 1, a lithium secondary battery 100 may include an electrode assembly 40 having a separator 30 between a positive electrode 10 and a negative electrode 20, and a case 50 in which the electrode assembly 40 is housed. The positive electrode 10, the negative electrode 20, and the separator 30 may be impregnated with an electrolyte (not shown).

[0090] The lithium secondary battery according to an embodiment may be capable of being charged at a high voltage or may be suitable for being driven at a high voltage. For example, the charging voltage of the lithium secondary battery may be 4.45 V or more, such as 4.45 V to 4.7 V, 4.45 V to 4.6 V, or 4.45 V to 4.55 V. By applying the positive electrode active material according to an embodiment, the lithium secondary battery can significantly reduce the amount of gas generated even when charged at a high voltage, and can achieve high capacity and long life characteristics.

[0091] negative electrode The negative electrode can include a current collector and a negative electrode active material layer located on the current collector, the negative electrode active material layer including a negative electrode active material and can further include a binder, a conductive material, or a combination thereof.

[0092] negative electrode active material The negative electrode active material includes a material capable of reversibly inserting / desorbing lithium ions, lithium metal, an alloy of lithium metal, a material dopable and dedopable with lithium, or a transition metal oxide.

[0093] Examples of the material capable of reversibly inserting / desorbing the lithium ions include carbon-based negative electrode active materials, which may include, for example, crystalline carbon, amorphous carbon, or a combination thereof. Examples of the crystalline carbon include graphite such as amorphous, plate-like, flaky, spherical, or fibrous natural graphite or artificial graphite, and examples of the amorphous carbon include soft carbon or hard carbon, mesophase pitch carbide, calcined coke, and the like.

[0094] As the alloy of the lithium metal, an alloy of lithium and a metal selected from Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al, and Sn can be used.

[0095] As the material dopable and dedopable with lithium, an Si-based negative electrode active material or an Sn-based negative electrode active material can be used. The Si-based negative electrode active material can be silicon, a silicon-carbon composite, SiOx (0 < x < 2), an Si-Q alloy (where Q is an element selected from alkali metals, alkaline earth metals, Group 13 elements, Group 14 elements (excluding Si), Group 15 elements, Group 16 elements, transition metals, rare earth elements, and combinations thereof, for example, Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Tl, Ge, P, As, Sb, Bi, S, Se, Te, Po, and combinations thereof), or a combination thereof. The Sn-based negative electrode active material can be Sn, SnO2, an Sn alloy, or a combination thereof.

[0096] The silicon-carbon composite may be a composite of silicon and amorphous carbon. The average particle size (D 50 ) may be, for example, 0.5 μm to 20 μm. According to one embodiment, the silicon-carbon composite may be in the form of silicon particles and the surfaces of the silicon particles coated with amorphous carbon. For example, it may include secondary particles (cores) formed by granulating primary silicon particles, and an amorphous carbon coating layer (shell) located on the surfaces of the secondary particles. The amorphous carbon may also be located between the primary silicon particles, for example, the primary silicon particles may be coated with amorphous carbon. The secondary particles may be present dispersed in an amorphous carbon matrix.

[0097] The silicon-carbon composite may further include crystalline carbon. For example, the silicon-carbon composite may include a core including crystalline carbon and silicon particles, and an amorphous carbon coating layer located on the surface of the core. The crystalline carbon may be artificial graphite, natural graphite, or a combination thereof. The amorphous carbon may include soft or hard carbon, mesophase pitch carbide, calcined coke, etc.

[0098] When the silicon-carbon composite contains silicon and amorphous carbon, the silicon content may be 10% to 50% by weight and the amorphous carbon content may be 50% to 90% by weight, relative to 100% by weight of the silicon-carbon composite. When the composite contains silicon, amorphous carbon and crystalline carbon, the silicon content may be 10% to 50% by weight, the crystalline carbon content may be 10% to 70% by weight, and the amorphous carbon content may be 20% to 40% by weight, relative to 100% by weight of the silicon-carbon composite.

[0099] The thickness of the amorphous carbon coating layer may be 5 nm to 100 nm. 50) can be from 10 nm to 1 μm, or from 10 nm to 200 nm. The silicon particles may exist alone as silicon, or in the form of a silicon alloy, or in an oxidized form. The oxidized form of silicon can be represented by SiO x (0 < x < 2). At this time, the atomic content ratio of Si:O indicating the degree of oxidation can be from 99:1 to 33:67. In this specification, unless otherwise defined, the average particle size (D 50 ) means the diameter of the particle with a cumulative volume of 50% by volume in the particle size distribution.

[0100] The Si-based negative electrode active material or the Sn-based negative electrode active material can be used by mixing with a carbon-based negative electrode active material. The mixing ratio when the Si-based negative electrode active material or the Sn-based negative electrode active material and the carbon-based negative electrode active material are mixed and used can be from 1:99 to 90:10 by weight.

[0101] Binder The binder serves to make the negative electrode active material particles adhere well to each other and also make the negative electrode active material adhere well to the current collector. As the binder, a non-aqueous binder, an aqueous binder, a dry binder, or a combination thereof can be used.

[0102] Examples of the non-aqueous binder include polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene-propylene copolymer, polystyrene, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamideimide, polyimide, or a combination thereof.

[0103] The water-based binder may be selected from styrene-butadiene rubber, (meth)acrylated styrene-butadiene rubber, (meth)acrylonitrile-butadiene rubber, (meth)acrylic rubber, butyl rubber, fluororubber, polyethylene oxide, polyvinylpyrrolidone, polyepichlorohydrin, polyphosphazene, poly(meth)acrylonitrile, ethylene propylene diene copolymer, polyvinylpyridine, chlorosulfonated polyethylene, latex, polyester resin, (meth)acrylic resin, phenolic resin, epoxy resin, polyvinyl alcohol, and combinations thereof.

[0104] When an aqueous binder is used as the negative electrode binder, a cellulose-based compound capable of imparting viscosity may be further included. As the cellulose-based compound, one or more of carboxymethylcellulose, hydroxypropylmethylcellulose, methylcellulose, or alkali metal salts thereof may be mixed and used. As the alkali metal, Na, K, or Li may be used.

[0105] The dry binder can be a fiberizable polymeric material such as polytetrafluoroethylene, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyethylene oxide, or combinations thereof.

[0106] Conductive material The conductive material is used to impart electrical conductivity to the electrodes, and may be any material that does not cause chemical changes in the battery and is electronically conductive. Specific examples include carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, ketjen black, carbon fibers, carbon nanofibers, and carbon nanotubes; metal-based materials in the form of metal powder or metal fibers, including copper, nickel, aluminum, and silver; conductive polymers such as polyphenylene derivatives; and mixtures thereof.

[0107] The content of the negative electrode active material may be 95% to 99.5% by weight relative to 100% by weight of the negative electrode active material layer, and the content of the binder may be 0.5% to 5% by weight relative to 100% by weight of the negative electrode active material layer. For example, the negative electrode active material layer may contain 90% to 99% by weight of the negative electrode active material, 0.5% to 5% by weight of the binder, and 0.5% to 5% by weight of the conductive material.

[0108] Current collector The negative electrode current collector can include, for example, indium (In), copper (Cu), magnesium (Mg), stainless steel, titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni), zinc (Zn), aluminum (Al), germanium (Ge), lithium (Li), or alloys thereof, and can be in foil, sheet, or foam form. The thickness of the negative electrode current collector can be, for example, 1 μm to 20 μm, 5 μm to 15 μm, or 7 μm to 10 μm.

[0109] electrolyte The electrolyte for a lithium secondary battery can be, by way of example, an electrolytic solution, which can include a non-aqueous organic solvent and a lithium salt.

[0110] The non-aqueous organic solvent serves as a medium through which the ions involved in the electrochemical reactions of the battery can migrate. The non-aqueous organic solvent may be a carbonate-, ester-, ether-, ketone-, or alcohol-based solvent, an aprotic solvent, or a combination thereof.

[0111] Examples of the carbonate solvent include dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), methyl ethyl carbonate (MEC), ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), etc. Examples of the ester solvent include methyl acetate, ethyl acetate, n-propyl acetate, dimethyl acetate, methyl propionate, ethyl propionate, decanolide, mevalonolactone, valerolactone, caprolactone, etc. Examples of the ether solvent include dibutyl ether, tetraglyme, diglyme, dimethoxyethane, 2-methyltetrahydrofuran, 2,5-dimethyltetrahydrofuran, and tetrahydrofuran. Examples of the ketone solvent include cyclohexanone. Examples of the alcohol solvent include ethyl alcohol and isopropyl alcohol. Examples of the aprotic solvent include nitriles such as R-CN (R is a straight-chain, branched, or cyclic hydrocarbon group having 2 to 20 carbon atoms, and may contain a double bond, an aromatic ring, or an ether group); amides such as dimethylformamide; dioxolanes such as 1,3-dioxolane and 1,4-dioxolane; and sulfolanes.

[0112] The non-aqueous organic solvent may be used alone or in combination of two or more kinds. When using in combination of two or more kinds, the mixing ratio may be appropriately adjusted according to the desired battery performance, which is widely understood by those working in the field.

[0113] When a carbonate-based solvent is used, a cyclic carbonate and a chain carbonate can be mixed and used, and the cyclic carbonate and the chain carbonate can be mixed in a volume ratio of 1:1 to 1:9.

[0114] The non-aqueous organic solvent may further include an aromatic hydrocarbon organic solvent. For example, the carbonate solvent and the aromatic hydrocarbon organic solvent may be mixed in a volume ratio of 1:1 to 30:1.

[0115] The electrolyte may further contain a vinyl ethyl carbonate, vinylene carbonate or ethylene carbonate based compound to improve the battery life.

[0116] Representative examples of the ethylene carbonate-based compounds include fluoroethylene carbonate, difluoroethylene carbonate, chloroethylene carbonate, dichloroethylene carbonate, bromoethylene carbonate, dibromoethylene carbonate, nitroethylene carbonate, and cyanoethylene carbonate.

[0117] Lithium salts are substances that dissolve in organic solvents and act as a source of lithium ions in the battery to enable basic lithium secondary battery operation and facilitate the movement of lithium ions between the positive and negative electrodes. Representative examples of lithium salts include LiPF6, LiBF4, LiSbF6, LiAsF6, LiClO4, LiAlO2, LiAlCl4, LiPO2F2, LiCl, LiI, LiN(SO3C2F5)2, Li(FSO2)2N (lithium bis(fluorosulfonyl)imide; LiFSI), LiC4F9SO3, LiN(C x F 2x+1 SO2)(C y F 2y+1 SO2) (x and y are integers from 1 to 20), lithium trifluoromethanesulfonate, lithium tetrafluoroethanesulfonate, lithium difluorobis(oxalato)phosphate (LiDFOB), and lithium bis(oxalato)borate (LiBOB).

[0118] The lithium salt is preferably used at a concentration within the range of 0.1 M to 2.0 M. If the lithium salt concentration is within the above range, the electrolyte has appropriate ion conductivity and viscosity, and therefore can exhibit excellent performance and allow lithium ions to migrate effectively.

[0119] Separator Depending on the type of lithium secondary battery, a separator may be present between the positive electrode and the negative electrode. As such a separator, polyethylene, polypropylene, polyvinylidene fluoride, or a multilayer film of two or more layers of these may be used, and it is of course possible to use a mixed multilayer film such as a two-layer separator of polyethylene / polypropylene, a three-layer separator of polyethylene / polypropylene / polyethylene, or a three-layer separator of polypropylene / polyethylene / polypropylene.

[0120] The separator may include a porous substrate and a coating layer including an organic material, an inorganic material, or a combination thereof located on one or both sides of the porous substrate.

[0121] The porous substrate may be a polymer membrane formed of any one polymer selected from polyolefins such as polyethylene and polypropylene, polyesters such as polyethylene terephthalate and polybutylene terephthalate, polyacetal, polyamide, polyimide, polycarbonate, polyether ketone, polyaryl ether ketone, polyetherimide, polyamide imide, polybenzimidazole, polyethersulfone, polyphenylene oxide, cyclic olefin copolymer, polyphenylene sulfide, polyethylene naphthalate, glass fiber, Teflon (registered trademark), and polytetrafluoroethylene, or a copolymer or mixture of two or more of these polymers.

[0122] The porous substrate can have a thickness of about 1 μm to 40 μm, for example, 1 μm to 30 μm, 1 μm to 20 μm, 5 μm to 15 μm, or 10 μm to 15 μm.

[0123] The organic material may include a (meth)acrylic copolymer including a first structural unit derived from (meth)acrylamide, a structural unit derived from (meth)acrylic acid or a (meth)acrylate, and a second structural unit including at least one of a structural unit derived from (meth)acrylamidosulfonic acid or a salt thereof.

[0124] The inorganic material may include, but is not limited to, inorganic particles selected from Al2O3, SiO2, TiO2, SnO2, CeO2, MgO, NiO, CaO, GaO, ZnO, ZrO2, Y2O3, SrTiO3, BaTiO3, Mg(OH)2, boehmite, and combinations thereof. The average particle size (D 50 ) may be 1 nm to 2000 nm, for example, 100 nm to 1000 nm, or 100 nm to 700 nm.

[0125] The organic material and the inorganic material may be mixed in one coating layer, or may be stacked in a coating layer including an organic material and a coating layer including an inorganic material.

[0126] The thickness of each of the coating layers may be from 0.5 μm to 20 μm, for example, from 1 μm to 10 μm, or from 1 μm to 5 μm.

[0127] Examples of the present invention and comparative examples are described below. The following examples are merely illustrative of the present invention, and the present invention is not limited to the following examples.

[0128] Example 1 1. Manufacturing of positive electrode active material (1) Preparation of the first positive electrode active material Ni 0.75 Mn 0.23 Al 0.02 (OH)2 and LiOH were mixed in a molar ratio of 1:1.05 and subjected to a first heat treatment at 850°C for 8 hours in an oxygen atmosphere to obtain a composition of Li 1.05 Ni 0.75 Mn0.23 Al 0.02 O2 and the average particle size (D 50 A first composite oxide having a secondary particle shape with a particle size of about 14 μm was prepared.

[0129] Aluminum sulfate was added to a distilled water solvent, and then the first composite oxide was added thereto and mixed for about 20 to 60 minutes. At this time, the aluminum content in the aluminum sulfate was designed to be 1.0 mol% relative to 100 mol% of the total metals excluding lithium in the final first positive electrode active material. After removing the solvent from the mixed solution and drying at 190°C, zirconium oxide was added to the obtained material and a second heat treatment was performed at 825°C for 8 hours in an oxygen atmosphere to prepare a first positive electrode active material. The zirconium content in the zirconium oxide was designed to be 0.2 mol% relative to 100 mol% of the total metals excluding lithium in the final first positive electrode active material. FIG. 2 is a scanning electron microscope photograph of the prepared first positive electrode active material.

[0130] (2) Preparation of the second positive electrode active material Ni 0.75 Mn 0.23 Al 0.02 (OH)2, LiOH and Al2O3 were mixed in a molar ratio of 1:1:0.02 and heat-treated in an oxygen atmosphere at 850℃ for 8 hours to obtain a composition of LiNi 0.7 Mn 0.2 Al 0.02 O2 and the average particle size (D 50 A second composite oxide having a single particle shape and a particle size of about 3 μm was produced.

[0131] The second composite oxide was mixed with Al2O3 and Y2O3 and heat-treated in an oxygen atmosphere at 825℃ for 8 hours to produce a second positive electrode active material. At this time, the final second positive electrode active material was mixed so that the coating aluminum was 0.4 mol% and the yttrium was 0.1 mol% relative to 100% by weight of the total metals excluding lithium. Figure 3 is a scanning electron microscope image of the produced second positive electrode active material.

[0132] (3) Manufacturing the final positive electrode active material The first and second positive electrode active materials were mixed in a weight ratio of 7:3 to prepare a final positive electrode active material.

[0133] 2. Manufacturing of the positive electrode 98.5 wt% of the prepared positive electrode active material, 1.0 wt% of polyvinylidene fluoride binder, and 0.5 wt% of carbon nanotube conductive material were mixed to prepare a positive electrode active material layer slurry, which was then coated on an aluminum foil current collector, dried, and rolled to prepare a positive electrode. The density of the final rolled positive electrode was about 3.52 g / cc.

[0134] 3. Manufacturing of lithium secondary batteries A negative electrode active material layer slurry was prepared by mixing 97.5 wt% graphite negative electrode active material, 1.5 wt% carboxymethyl cellulose, and 1 wt% styrene-butadiene rubber in an aqueous solvent. The negative electrode active material layer slurry was coated on a copper foil current collector, and then dried and rolled to prepare a negative electrode.

[0135] A polytetrafluoroethylene separator was used, and a lithium secondary battery was fabricated in a conventional manner using an electrolyte prepared by dissolving 1M LiPF6 in a solvent containing a mixture of ethylene carbonate and dimethyl carbonate in a volume ratio of 3:7.

[0136] Example 2 A positive electrode active material, a positive electrode, and a lithium secondary battery were manufactured in substantially the same manner as in Example 1, except that the content of yttrium in the yttrium oxide coating agent in the final second positive electrode active material was designed to be 0.2 mol % based on 100 wt % of the total metals excluding lithium.

[0137] Example 3 A positive electrode active material, a positive electrode, and a lithium secondary battery were manufactured in substantially the same manner as in Example 1, except that in the preparation of the second positive electrode active material, the content of aluminum in the aluminum oxide coating agent was designed to be 0.2 mol % based on 100 wt % of the total metals excluding lithium in the final second positive electrode active material.

[0138] Example 4 A positive electrode active material, a positive electrode, and a lithium secondary battery were manufactured in substantially the same manner as in Example 1, except that the content of aluminum in the aluminum oxide coating agent in the final second positive electrode active material was designed to be 0.6 mol % based on 100 wt % of the total metals excluding lithium.

[0139] Example 5 A positive electrode active material, a positive electrode, and a lithium secondary battery were manufactured in substantially the same manner as in Example 1, except that in the preparation of the first positive electrode active material, the zirconium content in the zirconium oxide coating agent was designed to be 0.1 mol % relative to 100 mol % of the total metals excluding lithium in the final first positive electrode active material.

[0140] Example 6 A positive electrode active material, a positive electrode, and a lithium secondary battery were manufactured in substantially the same manner as in Example 1, except that in the preparation of the first positive electrode active material, the zirconium content in the zirconium oxide coating agent was designed to be 0.3 mol % relative to 100 mol % of the total metals excluding lithium in the final first positive electrode active material.

[0141] Comparative Example 1 A positive electrode active material, a positive electrode, and a lithium secondary battery were manufactured in substantially the same manner as in Example 1, except that yttrium oxide was not used as a coating agent in the manufacture of the second positive electrode active material.

[0142] Comparative Example 2 A positive electrode active material, a positive electrode, and a lithium secondary battery were manufactured in substantially the same manner as in Example 1, except that the yttrium content in the yttrium oxide coating agent in the final second positive electrode active material was designed to be 1.5 mol % based on 100 wt % of the total metals excluding lithium.

[0143] Comparative Example 3 A positive electrode active material, a positive electrode, and a lithium secondary battery were manufactured in substantially the same manner as in Example 1, except that aluminum oxide was not used as a coating agent in the manufacture of the second positive electrode active material.

[0144] Comparative Example 4 A positive electrode active material, a positive electrode, and a lithium secondary battery were manufactured in substantially the same manner as in Example 1, except that in the preparation of the second positive electrode active material, the aluminum content in the aluminum oxide coating agent was designed to be 3 mol % based on 100 wt % of the total metals excluding lithium in the final second positive electrode active material.

[0145] Reference example 1 The first positive electrode active material was prepared as follows. 0.75 Mn 0.25 (OH)2, LiOH and Al2O3 were mixed in a molar ratio of 1:1:0.02 and heat-treated in an oxygen atmosphere at 850℃ for 8 hours to obtain a composition of LiNi 0.75 Mn 0.23 Al 0.02 O2 and the average particle size (D 50 A first composite oxide in the form of secondary particles having a particle size of about 14 μm was prepared. The first composite oxide was mixed with aluminum oxide powder and zirconium oxide powder, and the mixture was heat-treated in an oxygen atmosphere at 825° C. for 8 hours to prepare a first positive electrode active material coated with Al and Zr in a dry manner. A positive electrode active material, a positive electrode, and a lithium secondary battery were prepared in substantially the same manner as in Example 1, except that the first positive electrode active material was used.

[0146] Reference example 2 A positive electrode active material, a positive electrode, and a lithium secondary battery were prepared in substantially the same manner as in Example 1, except that the coating with aluminum sulfate was omitted in the preparation of the first positive electrode active material.

[0147] Reference example 3 A positive electrode active material, a positive electrode, and a lithium secondary battery were prepared in a manner substantially similar to that of Example 1, except that the coating with zirconium was omitted in the preparation of the first positive electrode active material, i.e., zirconium oxide was not added during the second heat treatment.

[0148] For ease of understanding, the design details of the positive electrode active materials in the examples, comparative examples, and reference examples are briefly shown in Table 1 below.

[0149] [Table 1]

[0150] Evaluation example 1 The lithium secondary batteries manufactured in the Examples, Comparative Examples, and Reference Examples were initially charged and discharged at a constant current of 0.2 C to 4.45 V and a constant voltage of 0.05 C at 25° C., and then discharged at 0.2 C to a cut-off voltage of 3.0 V. The initial discharge capacities are shown in Table 1 above.

[0151] Next, a cycle of charging at 1.0 C and discharging at 1.0 C in a voltage range of 3.0 V to 4.45 V at 45° C. was repeated 50 times or more, and the ratio of the 50 cycle discharge capacity to the initial discharge capacity was calculated, and is shown in Table 1 above.

[0152] Table 1 also shows the positive electrode mixture density in the rolled state for the examples, comparative examples, and reference examples.

[0153] Referring to Table 1, it can be seen that the examples achieved excellent initial discharge capacity and high positive electrode density, while also showing improved life characteristics compared to the comparative examples.

[0154] Although the preferred embodiments have been described in detail above, the scope of the present invention is not limited thereto, and various modifications and improvements made by those skilled in the art using the basic concepts defined in the claims also fall within the scope of the present invention. [Explanation of symbols]

[0155] 100 Lithium secondary battery 10 positive electrode 20 negative electrode 30 Separator 40 Electrode assembly 50 cases

Claims

1. A first positive electrode active material containing a lithium nickel-manganese based composite oxide having a nickel content of 60 mol % or more relative to 100 mol % of all metals excluding lithium, the first positive electrode active material being in the form of secondary particles formed by agglomeration of a plurality of primary particles; and The second positive electrode active material includes a lithium nickel-manganese-based composite oxide having a nickel content of 60 mol % or more relative to 100 mol % of all metals excluding lithium, and the second positive electrode active material is in the form of a single particle; the second positive electrode active material is located on a surface of the single particle and includes a coating layer containing aluminum and yttrium; the coating layer has an aluminum content of 0.1 mol % to 2 mol % and an yttrium content of 0.1 mol % to 1 mol % relative to 100 mol % of all metals excluding lithium in the second positive electrode active material.

2. The average particle size (D 50 ) is the average particle diameter (D 50 2. The positive electrode active material of claim 1 , wherein the positive electrode active material has a molecular weight of 1.0 or more.

3. The average particle size (D 50 ) is 10 μm to 20 μm, The average particle diameter (D 50 2. The positive electrode active material according to claim 1, wherein the particle size is 0.5 μm to 8 μm.

4. 2. The positive electrode active material according to claim 1, wherein the first positive electrode active material is included in an amount of 60% by weight to 95% by weight, and the second positive electrode active material is included in an amount of 5% by weight to 40% by weight, based on a total weight of the first positive electrode active material and the second positive electrode active material being 100% by weight.

5. The lithium nickel-manganese composite oxide of the first positive electrode active material and the lithium nickel-manganese composite oxide of the second positive electrode active material are the same or different, and each independently has a nickel content of 60 mol% to 80 mol% relative to 100 mol% of all metals excluding lithium. The positive electrode active material according to claim 1.

6. the lithium nickel-manganese composite oxide of the first positive electrode active material and the lithium nickel-manganese composite oxide of the second positive electrode active material are each independently a lithium nickel-manganese-aluminum composite oxide further containing aluminum in addition to nickel and manganese; 2. The positive electrode active material according to claim 1, wherein the lithium nickel-manganese-aluminum composite oxide has an aluminum content of 1 mol % to 3 mol % relative to 100 mol % of all metals excluding lithium.

7. The lithium nickel-manganese composite oxide of the first positive electrode active material and the lithium nickel-manganese composite oxide of the second positive electrode active material each independently have a cobalt content of 0 mol % to 0.01 mol % relative to 100 mol % of all metals excluding lithium. The positive electrode active material according to claim 1.

8. The lithium nickel-manganese composite oxide of the first positive electrode active material and the lithium nickel-manganese composite oxide of the second positive electrode active material are each independently represented by the following chemical formula 1: [Chemical formula 1] Li a1 Ni x1 Mn y1 Al z1 M 1 w1 O 2-b1 X b1 In Chemical Formula 1, 0.9≦a1≦1.8, 0.6≦x1≦0.8, 0.1≦y1≦0.4, 0≦z1≦0.03, 0≦w1≦0.3, 0.9≦x1+y1+z1+w1≦1.1, and 0≦b1≦0.1; M 1 is one or more elements selected from Al, B, Ba, Ca, Ce, Cr, Fe, Mg, Mo, Nb, Si, Sn, Sr, Ti, V, W, and Zr, and X is one or more elements selected from F, P, and S.

9. 9. The positive electrode active material according to claim 8, wherein in Chemical Formula 1, 0.6≦x1≦0.8, 0.1≦y1≦0.39, 0.01≦z1≦0.03, and 0≦w1≦0.29 are satisfied.

10. The positive electrode active material of claim 1 , wherein the first positive electrode active material further comprises a coating layer located on a surface of the secondary particle and containing aluminum and zirconium.

11. 11. The positive electrode active material of claim 10, wherein the coating layer has an aluminum content of 0.1 mol% to 2 mol% and a zirconium content of 0.05 mol% to 1 mol%, relative to 100 mol% of all metals excluding lithium in the first positive electrode active material.

12. The positive electrode active material according to claim 10 , wherein an aluminum content of the coating layer of the first positive electrode active material is greater than an aluminum content of the coating layer of the second positive electrode active material.

13. The positive electrode active material according to claim 12, wherein the aluminum content of the coating layer of the first positive electrode active material and the aluminum content of the coating layer of the second positive electrode active material are in a molar ratio of 5:1 to 2:

1.

14. The positive electrode active material of claim 10 , wherein the coating layer of the first positive electrode active material has a shell shape that continuously surrounds the surfaces of the secondary particles.

15. The cathode active material according to claim 10, wherein the coating layer of the first cathode active material has a thickness of 30 nm to 500 nm.

16. The positive electrode active material of claim 10 , wherein the coating layer of the first positive electrode active material further contains yttrium.

17. The positive electrode active material of claim 10 , further comprising a grain boundary coating portion located on a surface of a primary particle inside the secondary particle and containing aluminum.

18. The positive electrode active material of claim 1 , wherein the coating layer of the second positive electrode active material is in the form of a shell that continuously surrounds a surface of the single particle.

19. The cathode active material of claim 1 , wherein the coating layer of the second cathode active material has a thickness of 30 nm to 500 nm.

20. 10. The positive electrode active material of claim 1, wherein in the coating layer of the second positive electrode active material, aluminum is present in the form of a continuous film and yttrium is present in the form of islands.

21. 2. The cathode active material of claim 1, wherein the second cathode active material comprises a first coating layer located on a surface of the single particle and containing aluminum, and a second coating layer located on the first coating layer and containing yttrium.

22. 10. The cathode active material of claim 1, wherein the cathode active material is free of sodium.

23. A positive electrode current collector, and a positive electrode active material layer located on the positive electrode current collector, The positive electrode active material layer comprises the positive electrode active material according to any one of claims 1 to 22.

24. 24. The positive electrode of claim 23, wherein the positive electrode active material layer has a density of 3.5 g / cc to 3.7 g / cc.

25. The positive electrode according to claim 23 . a negative electrode, and A lithium secondary battery comprising an electrolyte.

26. 26. The lithium secondary battery according to claim 25, having a charging voltage of 4.45 V or higher.

Citation Information

Patent Citations

  • Modified ternary cathode material and preparation method thereof

    CN109755484A

  • Positive electrode active material for lithium secondary battery, and lithium secondary battery comprising same

    WO2022124774A1